Hyperbranched polyester polybenzoylcarbamate doped with palladium ions and its catalytic activity in hydrogenation reaction - Alina Vagapova; Aleksei Maksimov; Ernest Karalin; Gennadii Kutyrev (Discover Materials)
Abstract Metal complexes of hyperbranched polymers have attracted attention as potential catalysts due to their unique, tunable structure. Hyperbranched polyester polybenzoylcarbamate was synthesized by the reaction of second-generation hyperbranched polyester polyol with benzoyl isocyanate. The structure was studied by 1H, 13C NMR, and IR spectroscopies. The degree of functionalization as determined by 1H NMR spectroscopy was 25%. Reaction of palladium chloride with the synthesized ligand yielded a complex of hyperbranched polyester polybenzoylcarbamate was obtained for the first time. The participation of oxygen atom C = O of benzoyl fragments in coordination with Pd(II) ions was established by IR spectroscopy. The thermostability temperature of the synthesized ligand and complex was studied by thermogravimetric analysis and was found to be 124 °C. The mass content of palladium in complex is 14%, with the ratio of ligand: Pd = 1:2.7. The average particle size of complex as determined by electron microscopy is 1,8 ± 0,07 μm, and the complex forms cluster structures. Pd(II) ions in the complex were reduced to palladium nanoparticles in toluene hydrogen stream, followed by the study of hydrogenation of α-methylstyrene to isopropylbenzene under mild conditions, the activation energy was 61.2 kJ∙mol−1, and the selectivity reached 100%. Graphical Abstract